A method for noninvasive detection of fetal large deletions/duplications by low coverage massively parallel sequencing. (17th May 2013) - Chen, Shengpei; Lau, Tze Kin; Zhang, Chunlei; Xu, Chenming; Xu, Zhengfeng; Hu, Ping; Xu, Jian; Huang, Hefeng; Pan, Ling; Jiang, Fuman; Chen, Fang; Pan, Xiaoyu; et al.
ABSTRACT: Objective: To report the feasibility of fetal chromosomal deletion/duplication detection using a novel bioinformatic method of low coverage whole genome sequencing of maternal plasma. Method: A practical methodF etalC opy‐numberA nalysis through MaternalP lasmaS equencing (FCAPS), integrated with GC‐bias correction, binary segmentation algorithm and dynamic threshold strategy, was developed to detect fetal chromosomal deletions/duplications of >10 Mb by low coverage whole genome sequencing (about 0.08‐fold). The sensitivity/specificity of the resultant FCAPS algorithm in detecting deletions/duplications was firstly assessed in silico and then tested in 1311 maternal plasma samples from those with known G‐banding karyotyping results of the fetus. Results: Deletions/duplications, ranged from 9.01 to 28.46 Mb, were suspected in four of the 1311 samples, of which three were consistent with the results of fetal karyotyping. In one case, the suspected abnormality was not confirmed by karyotyping, representing a false positive case. No false negative case was observed in the remaining 1307 low‐risk samples. The sensitivity and specificity for detection of >10‐Mb chromosomal deletions/duplications were100% and 99.92%, respectively. Conclusion: Our study demonstrated FCAPS has the potential to detect fetal large deletions/duplications (>10 Mb) with low coverage maternal plasma DNA sequencing currently used for fetal aneuploidy detection. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Sequencing‐based noninvasive prenatal detection of fetal aneuploidy has been proven to be highly accurate. However, it is still a challenge to detect fetal deletion/duplication syndrome because of the interference from maternal DNA in maternal plasma. What does this study add? Here, we developed a practical bioinformatic methodology to detect fetal chromosomal deletions/duplications of >10 Mb using low coverage whole genome sequencing of maternal plasma.